Targeting the adipose tissue: heart crosstalk in pressure overload-induced heart failure: editorial - Tual-Chalot, Simon; Stellos, Konstantinos (Cardiovascular research, 2022)
This editorial refers to ‘Resistin deletion protects against heart failure injury by targeting DNA damage response’ by Zhao et al., https://doi.org/10.1093/cvr/cvab234.Following an excessive haemodynamic or metabolic stress, the heart initiates a compensatory adaptive response leading to the development of left ventricular hypertrophy.1 The persistence of this stress may lead to heart failure, a leading cause of mortality worldwide. Accumulating evidence from preclinical and clinical studies suggests that maladaptation of adipose tissue to stress conditions contributes to cardiac dysfunction and cardiovascular mortality. However, the underlying mechanisms are not completely understood.